Assessing the Impact of Deforestation on Agricultural Activities and Exploring Management Strategies in Benue South, Nigeria - Shamsu Abdullahi Idris; Nura Saleh; Lawan Kamiludeen Abba (CV Media Inti Teknologi, 2025)
Background of study: Deforestation has emerged as a major environmental and socio-economic concern, particularly in developing regions where agriculture serves as the primary livelihood. In Benue South, Nigeria, forest degradation is accelerating due to illegal logging, population pressure, and unregulated farming practices—posing a direct threat to agricultural productivity, food security, and rural livelihoods. Aims and scope of paper: This study aims to assess the perceived impact of deforestation on agricultural activities in Benue South and to identify appropriate community-based management strategies to mitigate its negative effects. The scope includes examining both environmental consequences and socio-economic responses from affected farming communities. Methods: A mixed-method approach was employed, combining structured questionnaires administered to 729 respondents across five Local Government Areas (LGAs) with Key Informant Interviews (KIIs). Data were analyzed using descriptive statistics and the Relative Importance Index (RII) to rank the severity of perceived deforestation impacts. Result: Findings reveal that deforestation has led to significant declines in crop yield, soil fertility, and food availability. Respondents also reported increased farm input costs and heightened migration pressure. RII analysis ranked decreased agricultural productivity and climate irregularities as the most critical consequences. Community awareness of forest regulations and reforestation practices was found to be low. Conclusion: Deforestation in Benue South has a profound negative effect on agriculture and rural stability. To address these challenges, integrated strategies such as participatory forest management, environmental education, and conservation-based farming should be prioritized. Policy alignment between local communities and environmental agencies is essential for sustainable land use.